CANNABIS USE IN THE UK: A QUANTITATIVE COMPARISON OF INDIVIDUAL DIFFERENCES IN MEDICAL AND RECREATIONAL CANNABIS USERS - Ciesluk, Beata; Erridge, Simon; Sodergren, Mikael H.; Troup, Lucy J. (Frontiers in Psychology, 2024)
There is a paucity of research, especially in the UK, which investigates individual differences in both medical and recreational cannabis users.A cross-sectional survey study design was used to assess recreational cannabis users and medical cannabis users currently living in the UK. Recreational cannabis users were invited to take part via social media.were recruited from Sapphire Medical Clinics, which provides treatment with prescribed cannabis-based medicinal products in the UK. Demographic data and cannabis use frequency, as well as post-traumatic stress disorder symptoms (PCL-5), depression symptoms (Centre for Epidemiological Studies Depression Scale), trait and state anxiety (State-Trait Anxiety Inventory), and cannabis use motives (Comprehensive Marijuana Motives Questionnaire) were collected. Chi-square and independent sample t-tests were used for comparison of categorical variables and normally distributed continuous variables. Data were analyzed using analyses of variance (ANOVAs) and t-tests. Statistical significance was considered where p<0.05.The survey was completed by 161 participants. Medical cannabis users were older, consumed cannabis more often, had a higher "Sleep" motive on the Comprehensive Marijuana Motives Questionnaire, and had a higher prevalence in self-reporting current diagnoses of neurological problems, mood disorders and anxiety disorders (p<0.05). Recreational cannabis users had higher scores on several motives for use (e.g., "Enjoyment", "Coping", "Experimentation", "Boredom", "Celebration") and higher state anxiety scores (p<0.05). The most common motives for cannabis use in both groups were "Enjoyment", "Low Risk" and "Sleep". There were no differences between groups in gender, "Low Risk" motive, post-traumatic stress disorder symptoms, depression scores, trait anxiety scores, self-reported prevalence of substance use related disorders, and past consumption of alcohol, tobacco, or caffeine (p>0.05).The current study demonstrates a difference in age and motivations for cannabis consumption between recreational and medical cannabis users, but also shows areas of potential overlap including mental health outcomes, past substance use, and gender. These UK-specific findings indicate that recreational cannabis users experience higher state anxiety highlighting the need for further evaluation of potential anxiogenic/anxiolytic properties of cannabis. These findings demonstrate the importance of researching individual differences in cannabis users, and hold significant implications for future research, clinical practice, and legislation.